Evaluation of a Standardized Nurse-Led Chest Tube Removal Protocol - Joanisse, Sonia (Université d'Ottawa / University of Ottawa, 2020)
Background: A nurse-led chest tube removal protocol (CTR) was implemented on two units. Aim: Evaluate the implementation of the protocol. Methods: A two-group cohort study was completed. Phase 1: Chest tube indwell time, length of stay, and complication rates were analyzed. Phase 2: A knowledge survey, chart reviews and observational audits were used to evaluate the uptake post-implementation. Findings: Phase 1: Reduction in chest tube indwell time (median 73.5 hours versus 52.7 hours, p = 0.0164) and length of stay (median 4.0 days versus 3.0 days, p = 0.0008) were noted in the post implementation group. Phase 2: Nurses completed patient assessments (n=22, 88% versus n=18, 72%) and teaching (n=22, 88% versus n=11, 56%) more frequently than they documented in the patient health record. Conclusion: Findings show that delegation of CTR to nurses with a standardized CTR protocol is safe and effective. Development of CTR documentation templates could improve documentation accuracy.
Keywords: Nurse-led; Chest tube removal; Standardized protocol; Implementation; Competency-based; Step wise learning